The effect of different tillage-fertilization practices on the mycoflora of wheat grains - Suproniene, Skaidre; Mankeviciene, Audrone; Kadziene, Grazina; Feiziene, Dalia; Feiza, Virginijus; Semaskiene, Roma; Dabkevicius, Zenonas (MTT Agrifood Research Finland, 2011)
A two-factor field experiment was carried out at the Lithuanian Institute of Agriculture during the period 2005-2008. The influence of different tillage and fertilization practices on wheat grain fungal contamination was evaluated. Grain surface contamination and internal grain infection with fungi were quantified using agar tests. Purified colonies were identified using different manuals. A total of 16 fungal genera were identified in spring and winter wheat grains. Alternaria infected 46.3% - 99.9%, Cladosporium 26.9% - 77.8%, Fusarium 0.9% - 37.1%, Penicillium 1.3% - 2.5% of grains tested. Winter wheat grain surface contamination by fungi ranged from 7.2 × 103 to 24.8 × 103 of colony forming units per g of grain (cfu g-1), spring wheat from 14.8 × 103 to 80.3 × 103 cfu g-1. No-tillage increased winter wheat grain infection by Alternaria, Aspergillus and Cladosporium species and total count of cfu g-1 on spring wheat grain surface. High fertilizer rates resulted in an increase in spring wheat grain infection by Fusarium and Penicillium species and total count of cfu g-1 on both spring and winter wheat grain surface.
Keywords: Ka; contamination; fungi; fertilization; grain; tillage; wheat